Pelatihan Penentuan Visi Misi Dan Action Plan Kepada Wirausaha Di Kota Salatiga - Atmanti, Hastarini Dwi; Fitria, Shoimatul (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2024)
This community service activity aims to provide training on vision and mission determination as well as action plans for entrepreneurs in the city of Salatiga, specifically for MSMEs (Micro, Small, and Medium Enterprises) in dairy processing and garment manufacturing. The choice of dairy processing and garment manufacturing MSMEs is due to the prominence of food and garment products in the city of Salatiga. Vision and mission determination training is conducted so that the efforts made by MSMEs can proceed in a clear direction and enhance the competitiveness of their products in the future. As many as 40 MSMEs participants spread across all sub-districts in the city of Salatiga took part in the community service activities. The training was conducted offline at Hotel Laras Asri Salatiga for 6 days. This community service is a synergy between the local government, academics, and MSMEs actors to make MSMEs better and more competitive.